Estimation of Phase Angle Jump (PAJ) for Different Types of Faults and Unbalancing in Distribution System - Fawad Shaikh, Muhammad; Ali Shah, Madad; Katyara, Sunny; Shankar Chowdhry, Bhawani (International Journal of Engineering and Technology, 2018)
Voltage sag caused by the faults in the power system has serious power quality issues and sometimes leads to interruption of power supply. The characteristics of voltage sag are its magnitude, time and phase angle jump (PAJ). This paper represents the estimation of phase angle jump (PAJ) when different types of faults are occurred in distribution system. Since the unbalancing is one of the major issues in distribution system that increases the zero sequence currents, over heats the distribution transformer, causes huge voltage drops in distributor etc. Therefore, the method used in this paper shows the PAJ when distributor is unbalance due to uneven loading or the line parameters of the distributor are unsymmetrical. Simple radial system is used to analyze the PAJ caused by the different types of faults and unbalancing. Different comparisons are made that are associated with PAJ such as PAJ vs fault impedance, zero sequence current and percentage of voltage unbalance. The research work is performed on MATLAB/SIMULINK to analyze the real time results.